Pengaruh Lingkungan Budaya Terhadap Implementasi Bisnis Skala Internasional - Yandi Suprapto; Figo Winnerko; Andrian Andrian; Jessyka Jessyka (STIE AMKOP, 2023)
Through data analysis, background information can help promote international business by considering the existing culture. In this paper, the author will elaborate on the importance of cultural elements in international business, how culture can affect international business strategy and marketing, as well as case studies on challenges and obstacles that arise. The research method used is data collection and processing from various sources, including online journals and websites relevant to the topic of discussion. In conclusion, the influence of culture is significant in the success or failure of international business. Losses are not uncommon in business, but the impact of culture on international business strategy affects various aspects such as communication, negotiation, decision-making, values-beliefs, business practices, consumer preferences, government regulations and policies, as well as human resource management. To succeed in international expansion, companies must conduct in-depth market and cultural research, adapt products and services, collaborate with local partners, comply with local laws and regulations, as well as develop cross-cultural communication and negotiation skills. Additionally, companies must be committed to ethical and socially responsible business practices, and be willing to learn and adapt to changes. Key Words: Cultural, Business, International